Solid state synthesis and characterization of LiFePO4/C as cathode material for Li-ion batteries - Karaman, Nejra; Aliefendić, Meho; Pljuco, Saša; Kozlica, Dževad; Nalić, Nađa; Korać, Fehim; Gutić, Sanjin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
Lithium transition metal phosphates have been recognized as potential positive electrodes for use in large scale production of lithium ion batteries, specially due to high thermal and chemical stability. Amongst all positive electrode materials, such as Li3V2(PO4)3, LiMnPO4 LiVPO4F, the olivine LiFePO4 has the most promising characteristics. The LiFePO4/C composite was synthesized by solid state reaction using LiOH as source of lithium ion, stearic acid which acts as reductive agent and carbon source and FePO4 precursor prepared from FeSO4×7H2O and NH4H2PO4. The starting materials were mixed in stoichiometric ratio and heated at 700°C under N2 flow to form the composite LiFePO4/C. Properties of synthesized material were analyzed by Raman spectroscopy, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Raman spectral analysis indicated some amorphous sp3 bonded carbon, sp2 graphite like phase and presence of carbides. Cyclic voltammograms confirmed good reversibility of intercalation and deintercalation of lithium ions from structure. Impedance response of the cells consisted of a depressed semicircle in the high frequency region, which is attributed to the charge-transfer process and sloping line in low frequency region which corresponds to the Warburg impedance.